(3GdJCUjd GdGSdGej ddOQGSGJ GdfaSjI (B:s (3GdHMK ai GdfaS GdGfSGfjI hGdefXhQ GdGSdGei (B/s - (3Jhajb, eMeO YRGdOjfs (al-Qahirah : Dar al-Salam, 1998)
Islam and psychological studies
Originally presented as the author's dissertation (doctoral) - al-Jami'ah al-Maghribiyah, Rabat
Keywords: Islam -- Psychology